The RE-LAYOUT DESIGN OF THE PRODUCTION MACHINE THROUGH BLOCPLAN AND SYSTEMATIC LAYOUT PLANNING (SLP) METHOD - Zandy Sholahudin Zaeni; Juniani, Anda Iviana; Zammi, Khafifulloh Al Faqih Zam (MEIN : Journal of Mechanical, Electrical & Industrial Technology, 2025)
Production machine layout arrangement at PT. Ometraco Arya Samanta requires new planning to increase the efficiency of space use. The method used is systematic layout planning (SLP), and Blocplan-90 can produce proposals for new production machine layouts with research results, including obtaining alternative production machine layouts. Second, reducing material handling distance. Designing the steel material production floor layout using the systematic layout planning (SLP) and Blocplan-90 methods considers the degree of close relationship between the machines used and the production process flow. Several aspects include area requirements, standard track width, and available area. The selection of alternative designs was based on criteria such as the total distance moved and the area used, where the selected alternative layout succeeded in producing increased efficiency in terms of the total reduction in distance moved. The area used compared to the initial layout. Alternative layout analysis shows that alternative layout 2 succeeded in reducing material handling movement distance by 34.68 meters or 22.24% and reducing area requirements by 74 meters or 18.6%, compared to the initial production machine layout.